2011
DOI: 10.1007/s10979-011-9271-7
|View full text |Cite
|
Sign up to set email alerts
|

Treating offenders with mental illness: A research synthesis.

Abstract: The purpose of this research synthesis was to examine treatment effects across studies of the service providers to offenders with mental illness. Meta-analytic techniques were applied to 26 empirical studies obtained from a review of 12,154 research documents. Outcomes of interest in this review included measures of both psychiatric and criminal functioning. Although metaanalytic results are based on a small sample of available studies, results suggest interventions with offenders with mental illness effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 51 publications
1
78
0
Order By: Relevance
“…Previous reviews which have focussed on violence reduction in a mental health population either took a broader approach to included diagnoses and outcomes or focus on mixed/ exclusively pharmacological interventions [19,20,21].…”
Section: Methodsmentioning
confidence: 99%
“…Previous reviews which have focussed on violence reduction in a mental health population either took a broader approach to included diagnoses and outcomes or focus on mixed/ exclusively pharmacological interventions [19,20,21].…”
Section: Methodsmentioning
confidence: 99%
“…The professional stakeholders of the TMHC believe recidivism is positively impacted by their efforts, but to my knowledge no evidence has been published. There is little evidence to support improved therapeutic outcomes in other MHCs, in part because few MHC evaluations include mental health outcomes, showing almost uniform preference for recidivism outcomes (Morgan et al, 2012). While the actual therapeutic validity of the courts is questionable, the framing of these new courts as therapeutic rests on more solid ground.…”
Section: Strategies Of Interventionmentioning
confidence: 99%
“…In their meta-analysis of 37 effect sizes from 25 studies assessing the effectiveness of interventions for justice-involved individuals with a mental illness, Martin et al 430 tentatively concluded that these interventions were modestly effective in reducing criminal justice involvement but had no significant effects on mental health service use, medication use, or mental health outcomes. In contrast, Morgan et al 431 synthesized treatment effects of interventions on criminal recidivism (ie, return to the criminal justice system) and psychiatric recidivism (ie, placement in a psychiatric hospital), finding strong positive treatment effects on general mental health symptoms and coping, and moderate effects on institutional adjustment and behavioral functioning. Mean effect sizes for criminal and psychiatric recidivism were inconclusive, however, and the review was limited by the quality of available research and limited numbers of RCTs.…”
Section: Care and Service Packages For Specific Subpopulationsmentioning
confidence: 99%
“…They further suggest that these findings demonstrate that traditional services are not the sole solution, and they argue for the design of a new generation of person-centered services tailored to the actual (rather than perceived) needs and risks of justice-involved individuals with serious mental illnesses. For example, there is emerging evidence that offenders with mental illness are equivalent in their criminal thinking 431 and antisocial attitudes 412 compared with nonmentally ill offenders. This suggests that in addition to their mental health needs, justice-involved individuals with serious mental illnesses have needs related to criminogenic characteristics that must be addressed.…”
Section: Care and Service Packages For Specific Subpopulationsmentioning
confidence: 99%